AUTOMOBILE CRASH BOX SYSTEM - GUNAYDIN, Kadir; TURKMEN, Halit Suleyman (2020)
he invention is related to a crash box system comprising "V" shaped leaf springs (2) located between the front plate (1) and the rear plate (3), wherein the leaf springs (2) have been placed vertical to the front plate (1) and rear plate (3) at the wing corners. Moreover, the system subject to the invention is related to a crash box system comprising a cylindrical bevelled tube (8) placed inside the outer tube (4) having an unconventional structure. The "V" shaped leaf springs (2), an outer crash box (outer tube) (4) having an unconventional structure, the re-entrant hexagonal bottom imperfections (12) and the re-entrant hexagonal top imperfections (13), a cylindrical tube (8) and cylindrical tube trigger mechanism (11) provided in the system subject to invention, enables energy absorption such that the peak forces are kept low at different times. By this means it is aimed to prevent, injuries and traumas that occur due to accident effects such as the whiplash effect during accidents at different speeds. La présente invention concerne un système de boîte-tampon comprenant des ressorts à lames en forme de "V" (2) situés entre une plaque avant (1) et une plaque arrière (3), les ressorts à lames (2) ayant été placés verticalement par rapport à la plaque avant (1) et à la plaque arrière (3) au niveau des coins d'aile. De plus, le système selon l'invention est associé à un système de boîte-tampon comprenant un tube biseauté cylindrique (8) placé à l'intérieur du tube externe (4) ayant une structure non conventionnelle. Les ressorts à lames en forme de "V" (2), une boîte-tampon externe (tube externe) (4) ayant une structure non conventionnelle, les imperfections de fond hexagonales rentrantes (12) et les imperfections supérieures hexagonales rentrantes (13), un tube cylindrique (8) et un mécanisme de déclenchement de tube cylindrique (11) disposés dans le système selon l'invention permettent une absorption d'énergie de telle sorte que les forces de crête sont maintenues basses à différents moments. Ainsi, la présente invention vise à prévenir des blessures et des traumatismes qui surviennent suite à un accident tels que l'effet du coup du lapin lors d'accidents à différentes vitesses.